2008
DOI: 10.1111/j.1523-536x.2008.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Operative Deliveries in Low‐Risk Pregnancies in The Netherlands: Primary versus Secondary Care

Abstract: The rate of operative deliveries was significantly lower for low-risk pregnant women who gave birth in a primary care setting compared with similar women who planned birth in secondary care. As with any retrospective analysis, it was not possible to eliminate bias, such as possible differences between primary and secondary care in assignment of risk status. In addition, known risk factors for interventions, technologies such as induction of labor and fetal monitoring, are only available in secondary care. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 9 publications
2
21
1
2
Order By: Relevance
“…Research has shown that there is a higher risk of obstetric interventions when giving birth in obstetric-led care (Janssen et al, 2002(Janssen et al, , 2007(Janssen et al, , 2009Maassen et al, 2008;Birthplace in England Collaborative Group, 2011). Green and Baston (2007) mentioned in their study a shift toward greater willingness to accept obstetric interventions, but are women aware of the fact that obstetric interventions are more likely when an obstetrician is providing care?…”
Section: Table 4cmentioning
confidence: 97%
See 1 more Smart Citation
“…Research has shown that there is a higher risk of obstetric interventions when giving birth in obstetric-led care (Janssen et al, 2002(Janssen et al, , 2007(Janssen et al, , 2009Maassen et al, 2008;Birthplace in England Collaborative Group, 2011). Green and Baston (2007) mentioned in their study a shift toward greater willingness to accept obstetric interventions, but are women aware of the fact that obstetric interventions are more likely when an obstetrician is providing care?…”
Section: Table 4cmentioning
confidence: 97%
“…We can safely assume that the majority of those 12% had a high-risk profile according to the LOI (e.g., diabetes, pre-existing hypertension, multiple pregnancies, and chronic diseases). However, the study of Maassen et al (2008) has shown that some women eligible for midwifery-led care gave birth in obstetric-led care despite having a low-risk profile. Although obstetric-led care is formally not an option for low-risk women, they are not being refused if they have a strong preference for giving birth under supervision of an obstetrician.…”
Section: Introductionmentioning
confidence: 95%
“…Some suggest that place of birth is not associated with mode of birth, 7,8 whilst others suggest an association with higher operative birth outcomes in larger volume or higher-level hospital facilities [9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…The effects of place of birth on birth outcomes have also been examined internationally. [6][7][8][9][10][11][12][13] In a systematic review, Hodnett et al 6 found that women receiving care in alternative compared with conventional birth settings were more likely to have a spontaneous vaginal birth without intervention. However, the authors were unable to draw conclusions about the independent effects of the design of the birth environment because of differences in the organisational aspects of the alternative settings.…”
Section: Introductionmentioning
confidence: 99%
“…Research undertaken in other resource rich settings includes a structured review by Walsh and Downe (2004), retrospective cohort studies in New Zealand (Davis et al, 2011) and The Netherlands (Maassen et al, 2008), and prospective cohort studies in Denmark (Overgaard et al, 2011) andEngland (Birthplace in England Collaborative Group, 2011). The results of the international research showed that overall, FMUs are associated with higher rates of spontaneous vaginal birth (Birthplace in England Collaborative Group, 2011;Maassen et al, 2008;Walsh and Downe, 2004), lower rates of instrumental births (Birthplace in England Collaborative Group, 2011;Maassen et al, 2008;Overgaard et al, 2011;Walsh and Downe, 2004), lower caesarean section rates (Maassen et al, 2008;Birthplace in England Collaborative Group, 2011;Overgaard et al, 2011), fewer labour interventions (Birthplace in England Collaborative Group, 2011;Walsh and Downe, 2004) and better breast-feeding rates (Walsh and Downe, 2004;Birthplace in England Collaborative Group, 2011) compared to similar-risk women planning to give birth at hospitals which cater for women with higherrisk pregnancies. In addition, there is no evidence to suggest that FMUs carry higher risk of perinatal morbidity for babies of women with low-risk pregnancies (Birthplace in England Collaborative Group, 2011;Overgaard et al, 2011;Walsh and Downe, 2004).…”
Section: Introductionmentioning
confidence: 99%